Synthesis of thiol-functionalized mesoporous calcium silicate and its adsorption characteristics for heavy metal ions. Issue 6 (December 2017) - Lihua, Liu; Li, Tong; Yang, Ganggang; Wang, Yifeng; Tang, Anping; Ling, Yulin
Graphical abstract: Highlights: Synthesis of thiol-functionalized mesoporous calcium silicate (MCS-SH) with slit-pore structure. MCS-SH possessed high adsorption capacity for Cu 2+, Pb 2+, Cd 2+, and Cr 3+ . The adsorption thermodynamic and kinetic characteristics of MCS-SH for heavy metals were explored. The relative adsorption thermodynamic and kinetic parameters of MCS-SH for heavy metal were obtained. An adsorption mechanism that included physical adsorption, chemical adsorption, and ion exchange was proposed. Abstract: Thiol-functionalized mesoporous calcium silicate (MCS-SH) was synthesized using post-grafting with calcium nitrate tetrahydrate and sodium metasilicate nonahydrate as raw materials, cetyl trimethyl ammonium bromide as template, and (3-mercaptopropyl)trimethoxysilane as modifying agent. The structure and composition were characterized using X-ray diffraction, Fourier-transform infrared spectroscopy, Brunauer–Emmett–Teller surface analysis, thermogravimetry–differential thermal analysis, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectrometry. The adsorption performance and thermodynamic and kinetic characteristics of MCS-SH for Cd 2+, Cu 2+, Pb 2+, and Cr 3+ were investigated. Results showed that MCS-SH possessed a slit-pore structure with a specific surface area of 129.32 m 2  g −1 and pore size that was mainly distributed in 5–49 nm, which reduced by 28.81 m 2  g −1 and 2 nm compared with those of unmodified mesoporous calcium silicate (MCS), respectively. The amount of SH grafted to MCS-SH was 0.4594 mmol g −1, according to the determined sulfur content. The maximum adsorption capacities for Cd 2+, Cu 2+, Pb 2+, and Cr 3+ were 601.51, 509.56, 618.09, and 334.81 mg g −1 at 293 K, respectively, which were much higher than those reported in the literature, and follow the order of Pb 2+  > Cd 2+  > Cu 2+  > Cr 3+ . The equilibrium data of the four heavy metal ions adsorbed by MCS-SH fitted the Langmuir model and, especially, the Redlich–Peterson model well. The adsorption processes were all endothermic, entropy increasing, and spontaneous. The adsorption of MCS-SH for Cd 2+, Cu 2+, Pb 2+, and Cr 3+ was rapid and attained equilibrium within 60 min. The adsorption kinetics can be well fitted by the pseudo-second-order model, and the adsorption activation energy followed the order of Cr 3+ (29.7526 kJ mol −1 ) > Pb 2+ (21.5840 kJ mol −1 ) > Cu 2+ (19.6988 kJ mol −1 ) > Cd 2+ (18.5377 kJ mol −1 ). The adsorption mechanisms include physical adsorption, chemical adsorption (especially surface complexing adsorption), and ion exchange, with chemical adsorption being the dominant mechanism. MCS-SH exhibited an excellent performance as adsorption material for Cd 2+, Cu 2+, Pb 2+, and Cr 3+ .